Sex life during pregnancy - Košec, Tamara (Obzornik zdravstvene nege, 2019)
Introduction: Pregnancy involves emotional and physiological changes, which affect the pregnant woman, her partner and their relationship. The sexuality of the couple changes with the onset of pregnancy compared to pre-pregnancy. The aim of the study was to investigate changes in the sex life of women during pregnancy. Methods: Quantitative research based on a questionnaire was carried out in August 2016 on a purposive sample of 685 women who had given birth at least once and women who were in the last trimester of pregnancy when completing the questionnaire. The data analysis included frequencies, percentages, mean values and independent samples t-test calculations. Results: The frequency of sexual intercourse decreased compared to the preconception period. The majority of women (43 %) included in the survey stated that their sexual desire declined during pregnancy. The most common factors that hindered women's sexual activity were fatigue and the feeling of awkwardness. Discussion and conclusion: Psychophysical changes in a pregnant woman may affect the couple's sexuality to a greater or lesser extent, which may in turn affect their relationship. It is therefore crucial that couples be offered quality counseling on sex life by appropriate institutions and programmes
Keywords: changes in pregnancy; nosečniške spremembe; partnership; partnerstvo; predporodno obdobje; prenatal period; sexuality; spolnost